Infectious Mononucleosis in Adults: Some Clinical and Epidemiological Features of Infectious Mononucleosis - Dziubenko, Nataliia (The Ukrainian Scientific Medical Youth Journal, 2025)
the article highlights the clinical and epidemiological features of infectious mononucleosis in adults based on an analysis of 222 patients who underwent treatment at the infectious diseases department of St. Michael’s Clinical Hospital in Kyiv from 2017 to 2023. Infectious mononucleosis is primarily caused by the Epstein-Barr virus, although other etiological agents include cytomegalovirus and human herpesvirus type 6. The aim of the study was to assess the incidence and epidemiological characteristics of infectious mononucleosis in adults over a six-year observation period. The research included a retrospective analysis of medical records, clinical manifestations, and laboratory-confirmed diagnoses. The study demonstrated that the incidence of infectious mononucleosis remained stable from 2017 to 2019, followed by a complete absence of cases in 2020 – 2021, likely due to the impact of pandemic restrictions related to coronavirus disease 2019. In 2022–2023, a resurgence of cases was observed, indicating the return of viral circulation. The average annual incidence rate was calculated at 34 cases per year, which aligns with epidemiological data reported in the literature. Among the analyzed patients, 57.3% were men and 42.7% were women, with the highest prevalence observed in the age group of 18 to 29 years, accounting for 70.3% of cases. The study found that Epstein-Barr virus was detected in 57.1% of male and 42.9% of female patients, whereas cytomegalovirus was more frequently identified in women (10.8%) than in men (4.5%). A significant proportion of patients (77.02%) were hospitalized with alternative preliminary diagnoses, primarily lacunar tonsillitis (36.5%), as well as follicular tonsillitis (2.5%), hepatitis (1.5%), meningitis (1.75%), and fever of unknown origin (0.5%). These findings indicate that infectious mononucleosis in adults often presents with a polymorphic clinical picture, which may complicate early diagnosis. Statistical analysis was performed using Student’s t-test, Wilcoxon W-test, the Chi-square method, and Spearman’s correlation coefficient, with a significance threshold of p=0.05. The results emphasize the need for improved differential diagnosis strategies, drawing clinicians’ attention to other manifestations of infectious mononucleosis, such as fever, generalized lymphadenopathy, and hepatosplenomegaly. The study highlights the role of infectious mononucleosis as a significant clinical disease in adults and substantiates the need for continuous epidemiological monitoring.